Dimensions of Caregiving in Schizophrenia - Fatima, Sahar; Tariq , Qudsia (Journal of the Dow University of Health Sciences (JDUHS), 2022)
Family plays a vital role in the lives of individuals living with mental illnesses like schizophrenia. Schizophrenia is a severely disabling mental illness which affects the functioning of family caregivers. Family caregivers of individuals with schizophrenia have received significant consideration in recent years due to robust family involvement in caregiving of ill individuals. The family environment reflects the estimate of psychosocial factors that anticipate the prognosis of illness. Not surprisingly, family caregiving is a prominent support system that displays diverse roles regarding caregiving of individuals with mental illness; however, it has been stayed overlooked by the mental health practitioners. Family caregivers of individuals living with schizophrenia have to deal with a number of problems, such as associated stigma, burnout and reduced quality of life. These problems are result from apparent role of caring when combined with inefficient support system and unproductive ways of coping. Subsequently, may affect the biopsychosocial integrity and quality of life of caregivers. It is now well recognised concern for a mental health professional to acknowledge various dimensions of caregiving and cater the needs associated with family caregivers of individuals with schizophrenia. This review article used a descriptive approach to develop qualitative themes of different dimensions of caregiving from the review of literature. This is a retrospective study which has given an overview of different dimensions of caregiving in context of individuals living with schizophrenia. It is important to pursue further research on this neglected public health concern of caregiving.